Pengembang Instrumen Tes Berbasis Literasi Sains Materi Fluida Statis Kelas XI SMA - Algiranto Algiranto (LPPM UNIVERSITAS PGRI SILAMPARI, 2022)
This study aims to (1) describe the characteristics of a test instrument based on scientific literacy of static fluid material for students of class XI SMA. (2) Describe the feasibility of a static fluid science literacy-based test instrument for students of class XI SMA. (3) Describe the results of teacher and student responses to tests based on static fluid science literacy for students in class XI SMA. This type of research is Research and Development (R&D). The research subjects were students of class XI SMA Negeri 3 Merauke. Data collection techniques used include tests, questionnaires, and documentation. The test instrument developed is in the form of a discourse description test that includes four categories of scientific literacy. The results of the characteristics of the scientific literacy-based test instrument are, there are four question indicators with the number of scientific literacy test questions developed as many as 20 essay questions with 4 main categories of scientific literacy, namely: Science knowledge, Investigation of the nature of science, Science as a way of thinking, Science Interaction, Technology , and Society. The questions have a scientific literacy category and are related to everyday life. Items have different levels of difficulty and scoring. The scientific literacy-based test instrument serves to measure the level of students' understanding. The feasibility of the developed test instrument was declared valid. The reliability of the scientific literacy-based test instrument developed in the reliable category.